Foucault and Weber on Leadership and the Modern Subject - Tahseen Kazi (Foucault Studies, 2017)
I propose in this paper that Foucault’s interest in parrhesia as a “technique of the self,” particularly in his reading of Cynic parrhesia, can be fruitfully taken as an exemplar for new political thought on leadership. I make my case by comparing parrhesia with Weber’s charisma, which is the only force Weber allows for inserting new valuations into traditional and rational-legal legitimate dominations. I propose that charisma and parrhesia not only share several key characteristics, but express an overabundance of identities. Although it is rarely acknowledged, I propose that this should hardly be surprising given Foucault’s longstanding interest in Weber’s work. Foucault’s governmentality can be productively set next to Weber’s psycho-sociology of modern man, Menschentum, to reveal the parallel courses taken by these two thinkers on the modern predicament. Both share a critical curiosity – one that revolves around Kant’s presentation in “What is Enlightenment?” – about life, and about seeing how we have come to be how we are as a philosophical problem. Yet, even with all of their parallels, particularly on the subject of leadership, the staggering difference between Foucault and Weber is that while Weber approached charisma as a possible therapy to the problem of the Menschentum being unable to derive new valuations from his rational-legal calculations, Foucault approached parrhesia by looking for techniques for confronting disciplined and biopolitical subjects within society with dangerous truths. Whereas conventional wisdom may presume that it is at such points as Weber’s charismatic leadership that Weber and Foucault would part ways, careful study shows that leadership is a point of connection between these two thinkers.